Induced variational method from supersymmetric quantum mechanics and the screened Coulomb potential - Drigo Filho, Elso [UNESP]; Ricotta, Regina Maria [UNESP] (World Scientific Publishing, 2000)
The formalism of supersymmetric quantum mechanics supplies a trial wave function to be used in the variational method. The screened Coulomb potential is analyzed within this approach. Numerical and exact results for energy eigenvalues are compared.
Keywords: analytic method; finite element analysis; methodology; nuclear physics; quantum mechanics; screening; variance